Visceral fat area as a prognostic biomarker in gastric cancer: a systematic review and meta-analysis of survival outcomes - Liu, Lei; Hou, Shufu; Yan, Bing; Hao, Ruiqi; Li, Linchuan; Song, Dandan (Frontiers in Oncology, 2025)
BackgroundVisceral fat area (VFA) has been suggested as an alternative to body mass index (BMI) for evaluating the effects of obesity and fat distribution. Although VFA has shown potential as a predictor of perioperative complications and surgical duration, its prognostic value in gastric cancer patients remains contentious. This meta-analysis aimed to elucidate the prognostic significance of VFA in this patient population.MethodsWe searched the PubMed, Cochrane Library, CNKI, and EMBASE databases, including literature published up to July 31, 2024, to investigate the prognostic implications of VFA in postoperative and non-surgical gastric cancer patients. Outcome measures encompassed overall survival (OS), relapse-free survival (RFS), disease free survival (DFS).ResultsA total of 6,054 eligible patients were selected from 12 studies. The results indicated a significant association between elevated VFA and improved OS and DFS/RFS (OS: HR 0.76, 95% CI 0.65-0.90, p = 0.001; DFS: HR 0.84, 95% CI 0.75-0.95, p = 0.004). Subgroup analyses were conducted to assess the robustness of these findings.ConclusionsThis meta-analysis demonstrated that among patients with gastric cancer who underwent surgery or other treatments, elevated VFA was significantly associated with improved OS and DFS/RFS. Consequently, VFA may serve as a useful prognostic indicator for assessing the prognosis of gastric cancer patients following treatment. However, further prospective studies are necessary to validate these findings and confirm the reliability of VFA as a prognostic marker.Systematic review registrationhttps://inplasy.com/, identifier INPLASY202490078.